2016
DOI: 10.1016/j.nlm.2015.11.014
|View full text |Cite
|
Sign up to set email alerts
|

Hippocampal noradrenergic activation is necessary for object recognition memory consolidation and can promote BDNF increase and memory persistence

Abstract: Previously we showed that activation of the Nucleus of the Solitary Tract (NTS)-Nucleus Paragigantocellularis (PGi)-Locus coeruleus (LC) pathway, which theoretically culminates with norepinephrine (NE) release in dorsal hippocampus (CA1 region) and basolateral amygdala (BLA) is necessary for the consolidation of object recognition (OR) memory. Here we show that, while the microinjection of the beta-noradrenergic receptor blocker timolol into CA1 impairs OR memory consolidation, the microinjection of norepineph… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
26
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 61 publications
(27 citation statements)
references
References 38 publications
1
26
0
Order By: Relevance
“…Noradrenergic signaling is known to be an important regulator of Bdnf expression. Application of norepinephrine to neurons in culture or injection of exogenous norepinephrine in vivo increases Bdnf expression (Chen et al 2007;Mello-Carpes et al 2016). A similar increase in hippocampal Bdnf expression is observed following treatment with antidepressants, including norepinephrine reuptake inhibitors such as reboxetine (Baj et al 2012;Larsen et al 2008;Musazzi et al 2009;Russo-Neustadt et al 2004).…”
Section: Glutamate Receptorsmentioning
confidence: 74%
See 1 more Smart Citation
“…Noradrenergic signaling is known to be an important regulator of Bdnf expression. Application of norepinephrine to neurons in culture or injection of exogenous norepinephrine in vivo increases Bdnf expression (Chen et al 2007;Mello-Carpes et al 2016). A similar increase in hippocampal Bdnf expression is observed following treatment with antidepressants, including norepinephrine reuptake inhibitors such as reboxetine (Baj et al 2012;Larsen et al 2008;Musazzi et al 2009;Russo-Neustadt et al 2004).…”
Section: Glutamate Receptorsmentioning
confidence: 74%
“…; Mello‐Carpes et al . ). A similar increase in hippocampal Bdnf expression is observed following treatment with antidepressants, including norepinephrine reuptake inhibitors such as reboxetine (Baj et al .…”
mentioning
confidence: 97%
“…Later Mello-Carpes et al (2016) endorse this result and showed that hippocampal norepinephrine acting on ß-adrenergic receptors is essential also for object recognition memory consolidation [12]. Its release depends on Nucleus of the Solitary Tract-Nucleus Paragigantocellularis-Locus coeruleus-CA1 region of dorsal hippocampus pathway has been mentioned earlier [13].…”
Section: Molecular Basis Of Hippocampus Memory Functionmentioning
confidence: 91%
“…Besides ß-noradrenergic mechanisms there is also hippocampal mechanisms mediated by brain-derived neurotrophic factor are important for the persistence of fear-motivated long-term memory and object recognition memory [2,12].…”
Section: Molecular Basis Of Hippocampus Memory Functionmentioning
confidence: 99%
“…The vagus nerve mediates visceral stimuli to the LC. The LC communicates with various brain regions via noradrenergic neurons, and activation of LC-noradrenergic pathways improves object recognition [60,61]. The effects of MHBAs on hippocampal NE signaling were further examined, and MHBAs were found to increase NE content and extracellular NE levels in the hippocampus.…”
Section: Mhbas Enhance Cognitive Function Via Activation Of the Vagusmentioning
confidence: 99%